(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
Technology has become an important asset in current society, where the use of mobile devices as supporting tools in the learning process is known as m-learning. Thus, the use of the cell phone can be seen as an educational tool for teaching reading and writing. For this reason, a quantitative study is proposed to analyze the applicability of the use of the cell phone as a supporting tool in the teaching and learning processes. Among the results, it stands out that working on the promotion and use of the cell phone as a tool for teaching reading and writing allows the use of functional and significant practices that reflect the use of the current resources promoted by the technological society.